Pengaruh Kualitas Pelayanan Dan Fasilitas Perpustakaan Sebagai Prediktor Terhadap Kepuasan Civitas Akademika Fakultas Ekonomi Universitas Tarumanagara Di Jakarta - M Tony Nawawi; Ida Puspitowati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The implementation of college must be equipped with facilities to support the success of the goal of a college program. One of the facilities to support the success of a university is the provision of a library. The aim of the study was to determine the effect of the services, facilities and library facilities on the satisfaction of visitors to the library. The research method used is non-probability sampling is judgmental sampling is a form of convenience sampling where the population elements are selected based on investigator assessment. The population in this study is the entire academic community untar, while the sample is the economics faculty of the academic community who've been/borrow at the library. While the analysis will be used multiple regression method. In accordance with the high college library functions required to provide quality services and facilities to meet the needs and expectations of library users. The library as an institution service provider is expected to meet users' satisfaction with the provision of various information resources and providing quality service and complete facilities.